Gunnar Optiks Study #2: Electromyography and Tear Volume. - Kundart, James; Hayes, John; Yu-Chi Tai; Sheedy, James E. (Optometry & Visual Performance, 2015)
Background: This study was conducted to study the difference between the classic Gunnar Optiks computer spectacles and control glasses with small changes in base curve or tint. Methods: Twenty-nine subjects, ages 22-62, completed this study. The two control pairs of eyeglasses were in similar frames, and both sets of lenses were made of similar resin with antireflective coating. One control pair had gray-tinted (neutral density) lenses made with the same optical power as the Gunnar Optiks design. The other had the same yellow tint but a flatter base curve and less faceform than the Gunnar design. Under stressful conditions of glare and dry air induced by a fan, electromyography of the eyelid to quantify squinting and blinking experienced with each type of glasses and tear volume measurement using Zone Quick phenol red thread were recorded. Conditions were compared with a mixed-model analysis of variance or covariance. Results: Statistical analysis revealed no significant difference between the Gunnar Optiks design and the control glasses under these conditions. There were no significant differences in squint power (F=1.88, p=0.083) and squint frequency (F=2.065, p=0.057) between the Gunnar Optiks design and the control eyeglasses with a neutral density tint or flatter base curve. There was significantly increased tear volume (F=3.65, p=0.031) and reduced blinking (F=2.57, p=0.019), but a lower blink rate is associated with dry eye. Conclusion: The classic Gunnar Optiks design was not shown tofulfill their claims of reducing asthenopia due to normalization of blink rate or squinting.